ANALISIS STRATEGI BAURAN PROMOSI DAN STRATEGI SALURAN DISTRIBUSI PADA UNIT KELOLA ARCHIPELAGO INTERNATIONAL PADA SITUASI PANDEMI COVID-19 KOTA DENPASAR, BALI - Fadillah Manuhutu; Ida Ayu Putri Widawati; Amirosa Ria Satiadji (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2022)
The objectives of this study are (1) to analyze the marketing promotion strategy of hotel products carried out by Aston Denpasar, Neo Denpasar, Quest Denpasar during the covid-19 pandemic, (2) to analyze the marketing distribution channel strategy carried out by Aston Denpasar, Neo Denpasar, Quest Denpasar during the covid-19 pandemic, (3) To determine the right promotion strategy and distribution channel strategy during the covid 19 pandemic. This research uses qualitative research. Data analysis uses SWOT analysis where SWOT analysis is a tool used to compile the company's strategic factors. The results of this study. (1) The strategy used three hotels is to carry out the same promotional mix, namely personal selling, advertising, sales promotion and publicity strategies. (2) The distribution channel strategy carried out by Aston Denpasar, Neo Denpasar and Quest Hotels is where the hotel determines the best distribution channel for its products to meet customer needs. Consumer needs used direct distribution and distribution through wholesale agents. (3) The marketing and distribution mix recommendation strategy through swot analysis is in a growth strategy through horizontal integration.